Tunneling in heterogeneous ground: an update of the PBE code accounting for the uncertainty in estimates of block quantities from site investigations. Issue 1 (1st January 2023) - Napoli, M L; Barbero, M
Abstract: Hard rock blocks embedded in a soft matrix can be found in many geological units. When tunneling in these heterogeneous formations, many technical problems can be caused by the presence of cobbles and boulders. These risks depend on the excavation method selected, and typically increase as the block content, dimension and frequency increase. Therefore, successful tunneling projects require cobble-boulder properties to be accurately predicted, in order to select the best tunneling method and design the most appropriate cutterhead. A recent and extensive statistically-based methodology was developed to estimate the probability of encountering rock blocks located totally or partially within the tunnel excavation area, resulting in a free executable code, named PBE. A significant limitation of this code is that it requires, among other input parameters, the block content expected within the tunnel zone. This parameter can be estimated from 1D (i.e. borings/scanlines) or 2D (i.e. geological maps, outcrops, photographs) measurements. However, the block quantity inferred from these measurements is generally affected by a high magnitude of error. In this paper, an extension of the PBE is presented, that accounts for the uncertainty in estimates of block quantities from site investigations. The updated version of the executable code is also provided.